Evaluation of native Trichoderma spp. against pathogens infecting small cardamom - Vijayan, A.K.; Nair, Rasmi B.; Rajendran, Ranju; Francis, Shony M.; Nair, Anu S.; Thomas, J. (Journal of Plantation Crops, 2015)
A survey was carried out during 2008-2009 period in the high ranges of Idukki district for isolation and in vitro screening of native Trichoderma spp. against Fusarium oxysporum and Colletotrichum gloeosporioides, pathogens of small cardamom. All the 29 isolates were plated against the two selected plant pathogens in order to test their antagonistic potential and were found to be inhibitive to the growth of F. oxysporum and C. gloeosporioides. In dual cultures, out of the 29 isolates, on seventh day the isolates CT-4, CT-5, CT-10, CT-15, CT-22 and CT-23 showed above 85 per cent reduction on the growth of Fusarium and on tenth day the isolates CT-13, CT-18 and CT-23 showed above 34 per cent reduction on the growth of Colletotrichum. The biomass, spore production, the production potential of siderophore, indole acetic acid (IAA) and hydrogen cyanide (HCN) of these isolates were also assessed. Some of the isolates showed better HCN, IAA and siderophores production. This information can be employed for the exploitation of these biocontrol agents in the high ranges of Idukki district of Kerala for management of the two potential fungal pathogens of small cardamom.